Forced vibroacoustic response of a cylindrical shell in an underwater acoustic waveguide. (1st April 2023) - Kha, Jamie; Karimi, Mahmoud; Maxit, Laurent; Skvortsov, Alex; Kirby, Ray
Abstract: An analytical approach is proposed to analyze vibroacoustics of an infinitely long thin cylindrical shell under line-distributed harmonic excitation immersed in an underwater waveguide formed by a free surface and a rigid floor. Equations of motion of the thin shell are modeled using Flügge's shell theory, the fluid–structure coupling is implemented with the image source method to account for the infinite reflections of acoustic waves off the waveguide boundaries and Graf's addition theorem is used to reconcile the coordinate systems of the image sources in the analytical expressions. The vibroacoustic response from the proposed analytical model is verified by numerical results obtained from a finite element model, showing excellent agreement. The analytical approach provides a computationally efficient tool for parametric investigation into the relative effects of the proximity of the free surface and/or rigid floor on the vibroacoustic behavior of the shell. Highlights: Vibroacoustics of a cylindrical shell in an underwater acoustic waveguide is studied. An analytical model based on the source-image method and Graf's theorem is proposed. Effect of different waveguide configurations on the response is demonstrated. Validity of Lloyd's analogy results is evaluated using the proposed rigorous model. Far field pressures generated by the vibrating shell and by a monopole are compared.